2020
DOI: 10.1002/acm2.13121
|View full text |Cite
|
Sign up to set email alerts
|

A review on medical imaging synthesis using deep learning and its clinical applications

Abstract: This paper reviewed the deep learning‐based studies for medical imaging synthesis and its clinical application. Specifically, we summarized the recent developments of deep learning‐based methods in inter‐ and intra‐modality image synthesis by listing and highlighting the proposed methods, study designs, and reported performances with related clinical applications on representative studies. The challenges among the reviewed studies were then summarized with discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 192 publications
(145 citation statements)
references
References 183 publications
(334 reference statements)
1
131
0
2
Order By: Relevance
“…In addition, RFs keep achieving very promising results in recent applications related to outcome prediction [135,[139][140][141][142][143], but also for other domains like image classification [113,144] or automatic treatment planning [100,[145][146][147]. Regarding other tasks where RFs were among the state-of-the-art methods a few years ago, like image synthesis [148][149][150] or segmentation [151,152], the community has now fully switched the attention to CNNs [5,153,154]. Nevertheless, in favor of RFs one could argue that they are easy to implement and less computationally expensive than CNNs (i.e., they can work in regular CPU).…”
Section: Random Forests (Rfs)mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, RFs keep achieving very promising results in recent applications related to outcome prediction [135,[139][140][141][142][143], but also for other domains like image classification [113,144] or automatic treatment planning [100,[145][146][147]. Regarding other tasks where RFs were among the state-of-the-art methods a few years ago, like image synthesis [148][149][150] or segmentation [151,152], the community has now fully switched the attention to CNNs [5,153,154]. Nevertheless, in favor of RFs one could argue that they are easy to implement and less computationally expensive than CNNs (i.e., they can work in regular CPU).…”
Section: Random Forests (Rfs)mentioning
confidence: 99%
“…For certain applications, such as image segmentation [154,157,158] or synthesis [5], CNNs are now considered the state-of-the-art methods [4]. Although the comparison of different algorithms on the same dataset is not so common, an excellent way to track the evolution of the state-of-the-art algorithms is to look at the challenges and competitions organised around specific topics.…”
Section: Convolutional Neural Network (Cnns)mentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the tremendous success of deep learning in computer vision, 24–27 deep learning‐based methods have been recently investigated for medical image reconstruction, 28–31 analysis, 32–36 and synthesis 37,38 . Studies have demonstrated deep learning‐based approaches significantly outperform over CS‐based methods for image reconstruction 39‐42 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Krämer et al proposed a fully automated segmentation algorithm using dual-echo, UTE MRI data (18). Machine learning-based and deep learningbased segmentation and synthetic CT (also known as pseudo CT) generation methods have been intensively studied for the last decades (19)(20)(21)(22), among which random forest-based method is one popular machine learning approach. The popularity of random forest arises from its appealing features, such as its capability of handling a large variety of features and enabling feature sharing of a multi-class classifier, robustness to noise and efficient parallel processing (23).…”
Section: Introductionmentioning
confidence: 99%